Potret Wanita ditengah Kemiskinan Modern - Abdul Muid (LP2M Sekolah Tinggi Agama Islam Ar-Rosyid Surabaya, 2018)
Women are honorable and dignified human beings, as Allah greatly glorifies the dignity of women before Allah SWT. In the Qur'an Allah SWT. Mention one of the letters of the Qur'an is the letter